A novel dual agonist of glucagon-like peptide-1 receptors and neuropeptide Y2 receptors attenuates fentanyl taking and seeking in male rats. (1st July 2021) - Zhang, Yafang; Rahematpura, Suditi; Ragnini, Kael H.; Moreno, Amanda; Stecyk, Kamryn S.; Kahng, Michelle W.; Milliken, Brandon T.; Hayes, Matthew R.; Doyle, Robert P.; Schmidt, Heath D.
Abstract: There has been a dramatic increase in illicit fentanyl use in the United States over the last decade. In 2018, more than 31, 000 overdose deaths involved fentanyl or fentanyl analogs, highlighting an urgent need to identify effective treatments for fentanyl use disorder. An emerging literature shows that glucagon-like peptide-1 receptor (GLP-1R) agonists attenuate the reinforcing efficacy of drugs of abuse. However, the effects of GLP-1R agonists on fentanyl-mediated behaviors are unknown. The first goal of this study was to determine if the GLP-1R agonist exendin-4 reduced fentanyl self-administration and the reinstatement of fentanyl-seeking behavior, an animal model of relapse, in rats. We found that systemic exendin-4 attenuated fentanyl taking and seeking at doses that also produced malaise-like effects in rats. To overcome these adverse effects and enhance the clinical potential of GLP-1R agonists, we recently developed a novel dual agonist of GLP-1Rs and neuropeptide Y2 receptors (Y2Rs), GEP44, that does not produce nausea-like behavior in drug-naïve rats or emesis in drug-naïve shrews. The second goal of this study was to determine if GEP44 reduced fentanyl self-administration and reinstatement with fewer adverse effects compared to exendin-4 alone. In contrast to exendin-4, GEP44 attenuated opioid taking and seeking at a dose that did not suppress food intake or produce adverse malaise-like effects in fentanyl-experienced rats. Taken together, these findings indicate a novel role for GLP-1Rs and Y2Rs in fentanyl reinforcement and highlight a potential new therapeutic approach to treating opioid use disorders. Highlights: Exendin-4 attenuates voluntary fentanyl taking and seeking in rats. Exendin-4 produces malaise-like effects in fentanyl-experienced rats. GEP44, an agonist of GLP-1Rs & Y2Rs, reduces fentanyl taking and seeking in rats. GEP44 does not produce malaise-like effects in fentanyl-experienced rats.